Effect of different frequencies weekly training on parameters of oxidative stress - Camila Baumer Tromm; Guilherme Laurentina da Rosa; Karoliny Bom; Izadora Mariano; Bruna Pozzi; Talita Tuon; Luciano Acordi da Silva; Ricardo Aurino Pinho (Universidade Federal de Santa Catarina, 2011)
During the muscle contraction induced by exercises there is an increase in the reactive oxygen species production, causing oxidative stress in several organs, including liver and heart. The exercise may can increases antioxidant defenses and decrease oxidative stress in these organs. However, the number of the sessions a week necessary to improve the parameters of oxidative stress is not to well defined. The aim of the study was to investigate the frequency effects of exercise performed two and three times a week on changes in biomarkers of oxidative stress in the liver and heart. Were used 18 male mice (CF1), young (30 to 35g) and divided into groups (n=6/group): not trained (NT) trained twice a week (T2) and trained three times a week (T3). The animals were subjected to training for eight weeks. Forty-eight hours after the last session, the animals were killed. The liver and heart were removed and stored in - 70°C. Were analyzed the thiobarbituric acid reactive substances, protein carbonyls, content of total thiols, superoxide dismutase, catalase and glutathione peroxidase. Our findings showed that the group T3 reduced oxidative damage. There was increase in content of total thiols, superoxide dismutase and catalase in the T3 group when compared to NT. The glutathione peroxidase activity showed no significant difference between groups. This study demonstrated that only the frequency of training performed three times a week was able to reduces oxidative damage and increases the efficiency of antioxidant system of mice.